BLASTING VIBRATION ANALYSIS OF HIGWALL SLOPE STABILITY IN TUTUPAN MINING, PT. ADARO INDONESIA - TURNIP (NIM : 12106037 PROGRAM), TONNI
Peak Particle Acceleration (PPA) is produced because of blasting operation, it can not be direct used as a seismic factor on slope stability analysis. Use of Peak Particle Acceleration as a seismic factor, it will produce low safety factor and will not appropriate from the fact at site (Wong, H. N & Pang, P.L.R, 1995). Use of acceleration consider dominant frequency of blasting vibration which be at interval 5 – 200 Hz, whereas the dominant frequency of earthquake vibration which be at interval 0,1 – 2 Hz (Scott et.al., 1996). Therefore, on this research, acceleration value that are used as seismic factor are filtered at 0,1 – 2 Hz, or another mean, acceleration values as seismic factor are obtained from peak particle acceleration at peak particle displacement (PPD). Therefore, to find out the ground vibration effect of slope stability, critical acceleration calculation for highwall slope Section 10, 10A, 11 and 11A, Mining Tutupan, PT. Adaro Indonesia can be done with empirical approach and slope stability analysis at limit equilibrium. Result of calculation refers that critical acceleration for each section has variation which depend on high and slope inclination.